Resin composition

The use of a zeolite-coated resin composition addresses the issues of moisture absorption and thermal expansion in under-fill materials, ensuring improved durability and stability in electronic devices.

JP2025015018APending Publication Date: 2025-01-30MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2023118071
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing liquid sealing agents used as under-fill materials face challenges with high moisture absorption and thermal expansion coefficients, which can lead to material degradation and performance issues in electronic devices.

Method used

A resin composition containing zeolite coated with a surface treatment agent, such as a silane coupling agent or polyvinyl alcohol, is used to reduce moisture absorption and thermal expansion, achieving a low thermal expansion coefficient of 35 ppm/k or less when cured.

Benefits of technology

The resin composition provides excellent moisture resistance and thermal stability, reducing the risk of material deformation and enhancing the durability of electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015018000001
    Figure 2025015018000001
Patent Text Reader

Abstract

To provide a resin composition with low hygroscopicity and low thermal expansion coefficients, suitable for use in electronic devices.SOLUTION: A resin composition contains a zeolite coated with a surface treatment agent and a matrix resin. When cured to a gel fraction of 80% or higher, the resin composition exhibits a water absorption rate of 15% or less and a thermal expansion coefficient of 35 ppm / K or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and more particularly to a liquid resin composition useful as an underfill material. [Background technology]

[0002] Liquid sealants used as underfill materials are required to have excellent injectability, adhesion, curing properties, storage stability, etc., and to be free of voids. In addition, the parts sealed with the liquid sealant are required to have excellent moisture resistance, thermal cycle resistance, reflow resistance, crack resistance, warping resistance, etc. In order to satisfy the above requirements, liquid sealants mainly composed of epoxy resins are widely used as underfill materials.

[0003] Furthermore, in order to improve the moisture resistance and thermal cycle resistance, particularly the thermal cycle resistance, of the area sealed with the liquid sealant, it is known that a filler made of an inorganic substance such as silica filler (hereinafter referred to as "inorganic filler") can be used in the liquid sealant to control the difference in thermal expansion coefficient between the substrate made of an organic material such as epoxy resin and the semiconductor element and to reinforce the bump electrodes (Patent Document 1). Specifically, Patent Document 1 discloses an underfill material for flip-chip semiconductor devices, which comprises (A) an epoxy resin, (B) a polyfunctional aliphatic epoxy having an average molecular weight of 200 or more and being liquid at room temperature, (C) a basic curing agent that is solid at 100°C, and (D) an inorganic filler. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-56070 A Summary of the Invention [Problem to be solved by the invention]

[0005] Liquid sealants using inorganic fillers such as silica fillers do not have a sufficiently low thermal expansion coefficient, and there is a demand for a further reduction in the thermal expansion coefficient from the viewpoint of thermal cycle resistance, etc. Zeolite is known as an inorganic filler with a low thermal expansion coefficient, but zeolite is highly hygroscopic, making it difficult to use it for electronic device applications such as underfill materials. Therefore, an object of the present invention is to provide a resin composition that has low moisture absorption and a low thermal expansion coefficient and can be suitably used for electronic equipment applications. [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that a resin composition containing a zeolite coated with a surface treatment agent and a matrix resin can solve the above problems. The present invention has been completed based on this finding.

[0007] That is, the present invention relates to the following. [1] A resin composition containing zeolite coated with a surface treatment agent and a matrix resin, the resin composition having a water absorption of 15% or less when cured to a gel fraction of 80% or more, and an average thermal expansion coefficient of 35 ppm / K or less when cured to a gel fraction of 80% or more. [2] The resin composition according to [1] above, wherein the zeolite has d6r as a CBU. [3] The resin composition according to the above [1] or [2], wherein the zeolite has a structure of an oxygen ring with 8 or less members. [4] The resin composition according to any one of the above [1] to [3], wherein the zeolite is a CHA-type zeolite. [5] The resin composition according to any one of the above [1] to [4], wherein the surface treatment agent is at least one selected from the group consisting of a silane coupling agent, an epoxy resin, and a polyvinyl alcohol resin. [6] The resin composition according to any one of the above [1] to [5], wherein the matrix resin is an epoxy resin. [7] The resin composition according to any one of the above [1] to [6], wherein the content of the zeolite in the resin composition is 25 mass % or more and 90 mass % or less in terms of solid matter. [8] The resin composition according to any one of the above [1] to [7], wherein the content of the matrix resin in the resin composition is 5% by mass or more and 50% by mass or less in terms of solid matter. [9] The resin composition according to any one of the above [1] to [8], which is for use as an underfill material. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition which has low moisture absorption and a low thermal expansion coefficient and can be suitably used for electronic equipment applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the contents thereof as long as it does not depart from the gist of the present invention.

[0010] The resin composition of the present invention contains zeolite coated with a surface treatment agent and a matrix resin.

[0011] <Coating treatment> The resin composition of the present invention contains zeolite coated with a surface treatment agent. By coating with the surface treatment agent, the pores of the zeolite can be physically filled, so that the intrusion of moisture into the pores of the zeolite can be suppressed, and as a result, the hygroscopicity of the zeolite can be suppressed. Therefore, any surface treatment agent can be used as long as it is a material that can physically fill and block the pores of the zeolite.

[0012] <Surface treatment agent> The surface treatment agent for zeolite is not particularly limited as long as it has the property of blocking the pores of zeolite as described above, but a material that further imparts a specific property to the pores is preferable. Specifically, in addition to the property of blocking the pores, a material that imparts hydrophobicity to the zeolite, a property of imparting water vapor barrier properties, etc. are preferable. In addition, a material that blocks the pores of zeolite and has the property of reducing the coefficient of thermal expansion (CTE) is preferable.

[0013] (Silane coupling agent) A suitable example of a surface treatment agent that blocks the pores of zeolite and imparts hydrophobicity to zeolite is a silane coupling agent. A silane coupling agent is an organosilicon compound that contains, in its structure, one or more reactive functional groups and one or more alkoxy groups bonded to silicon atoms, and can block the pores of zeolite and impart hydrophobicity to the zeolite. Examples of the reactive functional group in the silane coupling agent include an epoxy group, a (meth)acryloyl group, a mercapto group, a hydroxyl group, a carboxyl group, an amino group, an amide group, a vinyl group, an isocyanate group, and the like. Among these, the epoxy group, the hydroxyl group, the amino group, and the vinyl group are preferred in terms of imparting high blocking properties to the pores of the zeolite.

[0014] The content of the reactive functional group in the silane coupling agent is preferably 150 g / mol or more, more preferably 200 g / mol or more, and even more preferably 300 g / mol or more, from the viewpoint of the surface coverage of the coupling agent. The alkoxy group in the silane coupling agent preferably contains an alkoxy group having 4 to 10 carbon atoms, particularly preferably a hexaoxy group or an octaoxy group, from the viewpoint of imparting hydrophobicity. The silane coupling agent may have an organic functional group other than the reactive functional group and the alkoxy group bonded to the silicon atom, such as an alkyl group or a phenyl group.

[0015] From the viewpoints of efficiently blocking the pores of the zeolite and imparting hydrophobicity to the zeolite, the silane coupling agent preferably has a weight average molecular weight of 1,000 or more, more preferably 2,300 to 30,000, and even more preferably 3,000 to 20,000. The weight average molecular weight is measured by gel permeation chromatography (GPS) and is calculated as the weight average molecular weight in terms of the molecular weight of standard polystyrene.

[0016] The silane coupling agent may be an oligomeric organosilicon compound (organosiloxane compound) such as a dimer or trimer formed by hydrolysis and polycondensation of a part of an organosilicon compound. Examples of the silane coupling agent include mercapto group-containing oligomeric silane coupling agents formed by hydrolysis and polycondensation of a part of a mercapto group-containing silane compound such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane, and mercapto group-containing oligomeric silane coupling agents which are co-condensates of the above mercapto group-containing silane compound and an alkyl group-containing silane compound such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane; γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, epoxy group-containing oligomer-type silane coupling agents obtained by hydrolysis and polycondensation of a portion of an epoxy group-containing silane compound such as methyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, methyltri(glycidyl)silane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; epoxy group-containing oligomer-type silane coupling agents which are co-condensates of the above-mentioned epoxy group-containing silane compounds with alkyl group-containing silane compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane; and epoxy group-containing oligomer-type silane coupling agents obtained by ether-modifying a portion of these epoxy group-containing oligomer-type silane coupling agents. These may be used alone or in combination of two or more.

[0017] The oligomer-type silane coupling agent preferably has an alkoxy group content of 1 to 60 mass%, more preferably 3 to 50 mass%, and even more preferably 5 to 25 mass%, which can block the pores of the zeolite and impart hydrophobicity to the zeolite. Specific examples of the oligomer-type silane coupling agent include commercially available epoxy group-containing silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., such as "KBM-403", "X-41-1053", "X-41-1059A", "X-24-9590", "KBM-803", "X-41-1805", "X-41-1810", and "X-41-1818".

[0018] When the silane coupling agent is used, the content thereof is preferably 0.001 to 3 parts by mass, particularly preferably 0.005 to 1 part by mass, further preferably 0.01 to 0.5 parts by mass, and particularly preferably 0.015 to 0.3 parts by mass, relative to 100 parts by mass of the zeolite. When the content is equal to or more than the lower limit, the pores of the zeolite can be effectively blocked and the zeolite can be made hydrophobic, whereas when the content is equal to or less than the upper limit, the silane coupling agent does not bleed out.

[0019] (Polyvinyl alcohol resin) A suitable example of a surface treatment agent that blocks the pores of zeolite and imparts water vapor barrier properties to zeolite is a polyvinyl alcohol resin (hereinafter sometimes referred to as a "PVA resin"). The PVA-based resin is a resin obtained by saponifying a vinyl ester homopolymer or a copolymer of a vinyl ester and another monomer using an alkali catalyst or the like.

[0020] The saponification degree of the PVA resin of the present invention is preferably 60 mol% or more, more preferably 65 to 98 mol%, further preferably 67 to 90 mol%, and particularly preferably 69 to 88 mol%, as measured in accordance with JIS K 6726. When the saponification degree is equal to or more than the lower limit, sufficient crystallinity is obtained, which is suitable for blocking the pores of the zeolite. When the saponification degree is equal to or less than the upper limit, the mobility of the side chain due to the residual acetate group (hydrophobic group) in the molecule is suppressed, and suitable water vapor barrier properties are obtained.

[0021] The average degree of polymerization of the PVA resin is preferably 100 to 4000, more preferably 200 to 3000, and particularly preferably 300 to 1000. When the average degree of polymerization is equal to or higher than the lower limit, the pore blocking property of the zeolite increases. On the other hand, when the average degree of polymerization is equal to or lower than the upper limit, the viscosity of the aqueous solution of the PVA resin is low and the handling property is good. The average degree of polymerization can be measured in accordance with JIS K 6726.

[0022] (Epoxy resin) As the surface treatment agent, an epoxy resin, particularly a liquid epoxy resin, can be suitably used. The epoxy resin fills the pores of the zeolite and acts to suppress the intrusion of moisture into the pores. In addition, by using a resin with low thermal expansion as the epoxy resin, a resin composition with a low average thermal expansion coefficient can be obtained.

[0023] The epoxy resin is not particularly limited as long as it can block the pores of the zeolite and achieve low thermal expansion, and examples thereof include bisphenol A type epoxy resins, bisphenol F type epoxy resins, epoxy resins having an oxazolidone ring skeleton, novolac type epoxy resins, triglycidylaminophenol, tetraglycidyldiaminodiphenylmethane, hydrophthalic acid type epoxy resins, bisphenol S type epoxy resins, resorcinol type epoxy resins, hydroquinone type epoxy resins, bisphenoxyethanolfluorene type epoxy resins, bisphenolfluorene type epoxy resins, biscresolfluorene type epoxy resins, and the like. Among these, one or more epoxy resins selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, epoxy resins having an oxazolidone ring skeleton, novolac type epoxy resins, triglycidylaminophenol, and tetraglycidyldiaminodiphenylmethane are preferred in terms of achieving the effects of the present invention.

[0024] Moreover, the epoxy resin is preferably a liquid epoxy resin that is easy to handle. Here, "liquid" means that the epoxy resin has fluidity. Specifically, the viscosity of the liquid epoxy resin at 25°C is preferably 500 Pa·s or less, more preferably 300 Pa·s or less, and more preferably 0.1 Pa·s or more. By setting the viscosity within this range, the workability of the epoxy resin can be improved. The viscosity can be measured by applying periodic deformation (strain) to the sample using a rotational rheometer and detecting the resulting stress and phase difference.

[0025] The liquid epoxy resin may be a commercially available product. Examples of commercially available bisphenol A type epoxy resins (liquid epoxy resins) that are liquid at 25°C include jER827 (epoxy equivalent: 185 g / eq), jER828 (epoxy equivalent: 189 g / eq) (all manufactured by Mitsubishi Chemical Corporation), YD-127 (epoxy equivalent: 185 g / eq), YD-128 (epoxy equivalent: 189 g / eq) (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), EPICLON840 (epoxy equivalent: 185 g / eq), EPICLON850 (epoxy equivalent: 189 g / eq) (all manufactured by DIC Corporation), DER331 (epoxy equivalent: 187 / eq), DER332 (epoxy equivalent: 173 g / eq) (manufactured by The Dow Chemical Company), and the like. In addition, examples of commercially available bisphenol F type epoxy resins (liquid epoxy resins) that are liquid at 25°C include jER806 (epoxy equivalent 165g / eq), jER807 (epoxy equivalent 170g / eq) (all manufactured by Mitsubishi Chemical Corporation), YDF-170 (epoxy equivalent 170g / eq) (manufactured by Nippon Steel Chemical & Material Co., Ltd.), EPICLON830 (epoxy equivalent 170g / eq), EPICLON835 (epoxy equivalent 172g / eq) (all manufactured by DIC Corporation), and DER354 (epoxy equivalent 170g / eq) (all manufactured by The Dow Chemical Company). One of these may be used alone, or two or more may be used in combination.

[0026] <Method of coating with surface treatment agent> The method for coating zeolite with the above-mentioned surface treatment agent is not particularly limited as long as the method is capable of coating. For example, a solvent such as acetone is added to zeolite and stirred to obtain a zeolite slurry. Next, the above-mentioned surface treatment agent is added to the slurry and further stirred. Here, the content of zeolite in the slurry is preferably 0.1 to 10 mass%, more preferably 0.5 to 5 mass%. Then, the mixture is filtered and dried to obtain a coated zeolite. The solvent may be appropriately selected depending on the surface treatment agent. For example, when the surface treatment agent is a silane coupling agent, acetone is preferred, when it is an epoxy resin, toluene is preferred, and when it is polyvinyl alcohol, water is preferred. Other examples of the method include dissolving or dispersing the surface treatment agent in a solvent such as toluene, acetone, or water, and immersing the zeolite in the solution or dispersion (hereinafter sometimes referred to as a "solution, etc."), spraying the solution, etc. onto the zeolite, and brushing the solution, etc. onto the zeolite.

[0027] The zeolite coated with the surface treatment agent by the above method is preferably dried thereafter. There is no particular limitation on the drying method, and for example, the zeolite may be thinly spread on a pad or the like and dried by heating for a certain period of time. Specifically, the zeolite may be dried using an oven or the like at a temperature of 80 to 150°C, preferably 100 to 130°C, for about 60 to 120 minutes, preferably 80 to 100 minutes. If the filler aggregates after drying, it may be pulverized using a mortar, mill, or the like.

[0028] <Zeolite> The zeolite contained in the resin composition of the present invention is not particularly limited as long as the cured product obtained by curing the resin composition of the present invention has a low water absorption rate and a low average thermal expansion coefficient, but is preferably a spherical zeolite having d6r as CBU. Such a spherical zeolite can reduce the water absorption rate and the average thermal expansion coefficient in the cured product of the resin composition.

[0029] (Zeolite structure) Zeolite is a compound that contains silicon or aluminum and oxygen and has a TO4 unit (T element is an element other than oxygen that constitutes the framework) as a basic unit. Specific examples of zeolite include crystalline porous aluminosilicates, crystalline porous aluminophosphates (ALPOs), and crystalline porous silicoaluminophosphates (SAPOs), but the zeolite according to the embodiment of the present invention is an aluminosilicate. Zeolite is made up of structural units called Composite Building Units (hereinafter referred to as "CBUs"), which are made up of several (several to several tens) TO4 units connected together. This gives the zeolite regular channels (tubular pores) and cavities. In the present invention, the cavities are physically blocked to prevent water from entering the pores of the zeolite, thereby reducing the water absorption rate of the zeolite. The crystal structure of CBU and zeolite, which will be described later, can be shown by the code that specifies the structure of zeolite, as defined by the International Zeolite Association (IZA). The structure of zeolite can be identified using the Zeolite Structure Database 2018 Edition (http: / / www.iza-structure.org / databases / ) based on the X-ray diffraction pattern obtained by an X-ray structure analyzer (e.g., BRUKER's tabletop X-ray diffractometer D2PHASER).

[0030] (Zeolite framework) The skeleton of the zeolite according to the present invention has d6r as a CBU. By having d6r, it is easy to obtain a resin composition having a low thermal expansion coefficient when cured. As the CBU, examples of zeolites having d6r include AEI, AFT, AFV, AFX, AVL, CHA, EAB, EMT, ERI, FAU, GME, JSR, KFI, LEV, LTL, LTN, MOZ, MSO, MWW, OFF, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TSC, and zeolites having a -WEN type structure. Among these, from the viewpoint of easy control of particle size, zeolites having an 8-membered oxygen ring or less structure are particularly preferred. Zeolites having an 8-membered oxygen ring or less structure include zeolites having AEI, AFT, AFX, CHA, ERI, KFI, SAT, SAV, SFW, and TSC type structures. Among these, zeolites having AEI, AFX, CHA, and ERI type structures are particularly preferred, and zeolites having CHA type structures are most preferred, since the structure is stable even when the shape is controlled. In this specification, the structure having an 8-membered oxygen ring means a structure in which the number of oxygen elements is 8 when the number of oxygen elements is the largest among the pores composed of oxygen and T elements (elements other than oxygen that constitute the framework) that form the zeolite framework.

[0031] (Average thermal expansion coefficient of zeolite) The average thermal expansion coefficient of the zeolite according to the present invention is preferably low because the average thermal expansion coefficient of the resin composition can be easily reduced with a small amount of zeolite. In addition, it is also preferable that the amount of zeolite is small, so that various physical properties of the resin are unlikely to change due to the addition of zeolite. In particular, it is preferable that the thermal expansion coefficient of the zeolite is low because it can suppress the increase in viscosity of the resin composition of the present invention. Specifically, the average thermal expansion coefficient of the zeolite is usually less than 0 ppm / K, preferably -2 ppm / K or less, more preferably -3 ppm / K or less, even more preferably -5 ppm / K or less, particularly preferably -6 ppm / K or less, and most preferably -8 ppm / K or less.

[0032] On the other hand, the average thermal expansion coefficient of zeolite is preferably high in that the difference between the average thermal expansion coefficient of zeolite and that of the matrix resin is small and the zeolite and the matrix resin are not easily peeled off. Therefore, the average thermal expansion coefficient of zeolite is usually -1000 ppm / K or more, preferably -900 ppm / K or more, more preferably -800 ppm / K or more, even more preferably -700 ppm / K or more, particularly preferably -500 ppm / K or more, and especially preferably -300 ppm / K or more. And, in particular, when used for applications in contact with other materials such as sealing materials such as underfill materials and substrates, it is preferable that it is high, specifically, it is preferably -100 ppm / K or more, more preferably -50 ppm / K or more, even more preferably -40 ppm / K or more, particularly preferably -30 ppm / K or more, especially preferably -25 ppm / K or more, and most preferably -20 ppm / K or more. The average thermal expansion coefficient of zeolite can be measured by calculating the lattice constant using the X-ray diffractometer "D8ADVANCE" manufactured by BRUKER and the X-ray diffraction analysis software "JADE". In order to eliminate the influence of moisture desorption, the zeolite is usually measured in a dry state.

[0033] The average thermal expansion coefficient of zeolite is usually measured in the range of 50 to 100°C. That is, it is a numerical value that represents the displacement of the lattice constant per 1°C from the average lattice constant at 50°C and the average lattice constant at 100°C when the temperature of the zeolite is raised. Here, the average lattice constant at each temperature is the average value of the lattice constants of the a-axis, b-axis, and c-axis. The average thermal expansion coefficient is measured by gradually raising the temperature after waiting until the lattice constant stabilizes.

[0034] The matrix resin in the resin composition of the present invention generally has a large thermal expansion coefficient in the high temperature range. Therefore, the average thermal expansion coefficient of zeolite is preferably low, particularly when the temperature is raised to the high temperature range. Specifically, the average thermal expansion coefficient (high temperature range) in the range of 50 to 350°C is preferably -9.5 ppm / K or less, more preferably -10.0 ppm / K or less, and even more preferably -12.5 ppm / K or less. The average thermal expansion coefficient (high temperature range) of zeolite here is a numerical value representing the displacement of the lattice constant per 1°C from the average lattice constant at 50°C and the average lattice constant at 350°C when the zeolite is heated.

[0035] (Zeolite shape) The shape of the zeolite according to the present invention is preferably spherical, since this makes it easy to incorporate the zeolite into a resin composition while suppressing an increase in the viscosity of the resin composition. Specifically, the zeolite preferably has the following sphericity. That is, the sphericity of zeolite is preferably 0.6 or more, more preferably 0.65 or more, even more preferably 0.7 or more, and particularly preferably 0.8 or more. There is no particular upper limit to the sphericity, and the sphericity may be 1 or less. In addition, the sphericity of cubic zeolites, which are common in normal zeolites, is 0.58. In this application, the "sphericity" is the average value of 10 particles obtained by a scanning electron microscope (SEM). In this specification, "sphericity" is defined as "the ratio of the minimum diameter to the maximum diameter of a particle." The maximum diameter and the minimum diameter can be determined by observation with a scanning electron microscope (SEM).

[0036] (Zeolite framework density) The framework density of the zeolite to be produced in the present invention is not particularly limited as long as the effects of the present invention are not impaired. The framework density of the zeolite is preferably low in that the structural vibration of the zeolite is likely to occur and the average thermal expansion coefficient is likely to be low. Therefore, the framework density of the zeolite is preferably 17.0T / 1000Å or less. 3 Less than or equal to 16.0T / 1000Å, more preferably 3 The following is the result. On the other hand, it is preferable that the framework density of the zeolite is high in order to increase the structural stability of the zeolite. The framework density of the zeolite is preferably 12.0T / 1000Å. 3 More preferably, 13.0T / 1000Å or more 3 More preferably, 14.0T / 1000Å or more 3 When the framework density is within the above range, the zeolite can be used as a stable filler. The framework density refers to the number of T atoms present per unit volume of zeolite, and is a value determined by the structure of the zeolite. In this specification, the numerical values ​​described in the IZA Zeolite Structure Database 2017 Edition (http: / / www.iza-structure.org / databases / ) may be used.

[0037] Framework density: 16.0T / 1000Å 3 Larger, 17.0T / 1000Å 3 Examples of the following zeolites include zeolites of the ERI, LTL, LTN, MOZ, OFF, SAT, SSF and -WEN structure types. Framework density: 15.0T / 1000Å 3 Larger, 16.0T / 1000Å 3 Examples of the following zeolites include zeolites of the AEI, AFT, AFV, AFX, AVL, EAB, GME, LEV, MWW and SFW type structures. Framework density: 14.0T / 1000Å 3 Larger, 15.0T / 1000Å 3 Examples of zeolites that may be mentioned include zeolites of the CHA, KFI, SAS and SAV structure types. Framework density: 14.0T / 1000Å 3 Examples of zeolites falling within the following ranges include zeolites of EMT, FAU, JSR, SBS, SBT, and TSC type structures.

[0038] (Silica / Alumina Molar Ratio (SAR) of Zeolite) The silica / alumina molar ratio (sometimes referred to as "SAR", "Si / Al2 molar ratio", or "Si / Al2 ratio") of the zeolite according to the present invention is not particularly limited as long as the effects of the present invention are not impaired. The SAR (Si / Al2 ratio) of the zeolite is preferably high in order to increase the moisture resistance of the resin composite material described below and to facilitate control of the amount of counter cations. Thus, the SAR (Si / Al2 ratio) of the zeolite is usually 2 or more, preferably 3 or more, more preferably 3.5 or more, even more preferably 4 or more, particularly preferably 4.5 or more, and most preferably 5 or more. On the other hand, the SAR (Si / Al2 ratio) of zeolite is preferably low in terms of easy and inexpensive production. Therefore, the SAR (Si / Al2 ratio) of zeolite is usually 2000 or less, preferably 1000 or less, more preferably 500 or less, and further preferably 100 or less. When the Si / Al2 ratio is within the above range, the amount of counter cations is easily controlled, and the production cost of zeolite is also low.

[0039] (Zeolite counter cation) The counter cation of the spherical zeolite to be produced in the present invention is not particularly limited as long as the effect of the present invention is not impaired. The counter cation of the zeolite is usually a proton, an alkali metal ion, or an alkaline earth metal ion. Preferably, it is a proton or an alkali metal ion, more preferably, it is a proton, a Li ion, a Na ion, or a K ion. In the case of an alkali metal ion or an alkaline earth metal ion, the smaller the size, the more likely the zeolite is to exhibit an average thermal expansion coefficient of less than 0 ppm / K, so this is preferable. Among these, the counter cation of the zeolite is preferably a proton, since this makes it easier to reduce the average thermal expansion coefficient of the resin composite. That is, the zeolite is preferably a proton type or an alkali metal type, more preferably a proton type, a Li type, a Na type, or a K type.

[0040] (Zeolite crystallinity) The crystallinity of the zeolite to be produced in the present invention is not particularly limited as long as the effect of the present invention is not impaired. The reason is that it is assumed that the Composite Building Unit (CBU) is a factor that has a greater influence on the average thermal expansion coefficient of the epoxy resin composite than the structure specified by the IZA code. The crystallinity of the zeolite can be calculated by comparing a certain X-ray diffraction peak determined by an X-ray diffractometer (e.g., BRUKER's tabletop X-ray diffractometer D2PHASER) with the X-ray diffraction peak of the reference zeolite. A specific calculation example is the crystallinity of LTA-type zeolite in Scientific Reports 2016, 6, Article number: 29210.

[0041] (Zeolite content) The content of zeolite in the resin composition of the present invention is, in terms of solid matter, preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and especially preferably 50% by mass or more, based on the total amount of the resin composition, from the viewpoint of suppressing the increase in viscosity and lowering the thermal expansion coefficient. On the other hand, it is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less, and particularly preferably 70% by mass or less. In addition, when the resin composition contains a filler other than the zeolite of the present invention, the content of the zeolite of the present invention in the total filler is preferably 10 mass % or more, more preferably 30 mass % or more, and even more preferably 50 mass % or more, since this tends to reduce the thermal expansion coefficient of the cured product of the kneaded resin composition.

[0042] <Matrix resin> The matrix resin used in the resin composition of the present invention is not particularly limited as long as it exhibits the effects of the present invention, but from the viewpoint of further exhibiting the effects as a composite material, it is preferable to use at least one selected from the group consisting of epoxy resins and polyimide resins. In particular, when used as a sealant such as an underfill material, epoxy resins are preferable. Also, when used as a substrate, polyimide resins are preferable. From the viewpoint of maintaining both excellent physical properties of the resin and heat resistance (resistance to thermal expansion) of the cured resin composition, the amount of the resin contained in the resin composition of the present invention is preferably 5% by mass or more, more preferably 10% by mass or more, calculated as solid matter, based on the total amount of the composition, while being preferably 50% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less.

[0043] (Epoxy resin) As the epoxy resin used in the present invention, it is preferable to use an epoxy compound having an aromatic ring, such as a bisphenol A type skeleton, a bisphenol F type skeleton, or a biphenyl skeleton, since the thermal expansion coefficient of the cured product (hereinafter, may be simply referred to as the "cured product") obtained by curing the resin composition of the present invention is likely to be low. Specific examples include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, naphthalene ring-containing epoxy resins, epoxy resins having a dicyclopentadiene skeleton, phenol novolac type epoxy resins, cresol novolac type epoxy resins, triphenylmethane type epoxy resins, aminophenol type epoxy resins, aliphatic epoxy resins, and copolymer epoxy resins of aliphatic epoxy resins and aromatic epoxy resins. Among these, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, naphthalene ring-containing epoxy resins, and aminophenol type epoxy resins are preferred, and bisphenol A type epoxy resins, bisphenol F type epoxy resins, naphthalene ring-containing epoxy resins, aminophenol type epoxy resins, and biphenyl type epoxy resins are more preferred.

[0044] In the present invention, it is preferable to use a polyfunctional epoxy resin because the glass transition temperature of the cured product is easily increased. As the polyfunctional epoxy resin, glycidyl ether type polyfunctional epoxy resins such as various phenols such as phenol novolac resin, cresol novolac resin, bisphenol A novolac resin, dicyclopentadiene phenol resin, phenol aralkyl resin, naphthol novolac resin, biphenyl novolac resin, terpene phenol resin, heavy oil modified phenol resin, and various phenols and polyhydric phenol resins obtained by condensation reaction of various phenols with various aldehydes such as hydroxybenzaldehyde, crotonaldehyde, glyoxal, and epoxy resins produced from epihalohydrin and various phenolic compounds are preferable.

[0045] From the viewpoint of fluidity, the epoxy resin used in the present invention preferably has a viscosity of 5 Pa·s or less at 23°C, and more preferably 0.1 to 3 Pa·s. The method for measuring the viscosity of epoxy resins is specified in JIS K7233 (1986), and a single cylinder rotational viscometer method is suitable. The viscosity of the epoxy resin used in the present invention at 23°C may be measured using a B-type rotational viscometer ("LVDV-Pri", Brookfield, spindle: S62), which is one of the single cylinder rotational viscometer methods.

[0046] From the viewpoint of viscosity control, the epoxy resin preferably has an epoxy equivalent of 50 g / eq or more and 500 g / eq or less, more preferably 90 g / eq or more and 150 g / eq or less. The epoxy equivalent is preferably high in terms of excellent heat resistance. On the other hand, it is preferably low in terms of improving the filling property of the liquid composition and increasing the bonding property by filling, by lowering the melting point of the epoxy resin and lowering the viscosity. The epoxy resins may be used alone or in any combination and ratio of two or more kinds. When mixed, the epoxy equivalent is the equivalent of the mixture.

[0047] The content of the epoxy resin in the resin composition of the present invention is preferably low in that the content of inorganic fillers such as zeolite is relatively high and the thermal expansion coefficient is easily reduced. On the other hand, it is preferable that the content is high in that the excellent physical properties of the epoxy resin are easily maintained. Specifically, it is preferably 5% by mass or more, and more preferably 10% by mass or more, based on the total composition. On the other hand, it is preferably 50% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less.

[0048] (hardening agent) The resin composition of the present invention preferably further contains a curing agent. The curing agent is a substance that contributes to a crosslinking reaction between crosslinking groups of an epoxy resin. The curing agent is not particularly limited, and can be generally known as an epoxy resin curing agent. For example, phenol-based curing agents, amine-based curing agents such as aliphatic amines, polyetheramines, alicyclic amines, and aromatic amines, acid anhydride-based curing agents, amide-based curing agents, tertiary amines, imidazole and its derivatives, organic phosphines, phosphonium salts, tetraphenylboron salts, organic acid dihydrazides, halogenated boron amine complexes, polymercaptan-based curing agents, isocyanate-based curing agents, blocked isocyanate-based curing agents, and dicyandiamine compounds can be mentioned. From the viewpoint of imparting fluidity and fast curing, acid anhydride-based curing agents are preferred as the curing agent.

[0049] Specific examples of phenol-based hardeners include bisphenol A, bisphenol F, 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl ether, 1,4-bis(4-hydroxyphenoxy)benzene, 1,3-bis(4-hydroxyphenoxy)benzene, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl ketone, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, phenol novolac, bisphenol A novolac, o-cresol novolac, m-cresol novolac, p-cresol novolac, xylenol novolac, poly-p-hydroxystyrene, hydroquinone, resorcinol, catechol, t-butylcatechol, t-Butyl hydroquinone, fluoroglycinol, pyrogallol, t-butyl pyrogallol, allylated pyrogallol, polyallylated pyrogallol, 1,2,4-benzenetriol, 2,3,4-trihydroxybenzophenone, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, Examples include 1,8-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 2,4-dihydroxynaphthalene, 2,5-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,8-dihydroxynaphthalene, allylated products or polyallylated products of the above dihydroxynaphthalenes, allylated bisphenol A, allylated bisphenol F, allylated phenol novolak, and allylated pyrogallol.

[0050] Specific examples of amine-based curing agents include aliphatic amines such as ethylenediamine, 1,3-diaminopropane, 1,4-diaminopropane, hexamethylenediamine, 2,5-dimethylhexamethylenediamine, trimethylhexamethylenediamine, diethylenetriamine, iminobispropylamine, bis(hexamethylene)triamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, N-hydroxyethylethylenediamine, and tetra(hydroxyethyl)ethylenediamine. Examples of polyetheramines include triethylene glycol diamine, tetraethylene glycol diamine, diethylene glycol bis(propylamine), polyoxypropylene diamine, polyoxypropylene triamines, and the like. Examples of alicyclic amines include isophoronediamine, methacenediamine, N-aminoethylpiperazine, bis(4-amino-3-methyldicyclohexyl)methane, bis(aminomethyl)cyclohexane, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraoxaspiro(5,5)undecane, and norbornenediamine. Examples of aromatic amines include tetrachloro-p-xylylenediamine, m-xylylenediamine, p-xylylenediamine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, 2,4-diaminoanisole, 2,4-toluenediamine, 2,4-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diamino-1,2-diphenylethane, 2,4-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, m-aminophenol, m-aminobenzylamine, benzyldimethylamine, 2-dimethylaminomethylphenol, triethanolamine, methylbenzylamine, α-(m-aminophenyl)ethylamine, α-(p-aminophenyl)ethylamine, diaminodiethyldimethyldiphenylmethane, and α,α'-bis(4-aminophenyl)-p-diisopropylbenzene.

[0051] Specific examples of acid anhydride-based curing agents include dodecenyl succinic anhydride, polyadipic anhydride, polyazelaic anhydride, polysebacic anhydride, poly(ethyloctadecanedioic) anhydride, poly(phenylhexadecanedioic) anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylcyclohexene dicarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophthalic anhydride, and the like. Examples of the dianhydride include phenylene tetracarboxylic acid anhydride, ethylene glycol bistrimellitate dianhydride, HET acid anhydride, nadic acid anhydride, methylnadic acid anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic acid anhydride, 3,4-dimethyl-6-(2-methyl-1-propenyl)-4-cyclohexene-1,2-dicarboxylic acid anhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic acid dianhydride, and 1-methyl-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic acid dianhydride.

[0052] Examples of the amide-based curing agent include dicyandiamide and polyamide resins. Examples of tertiary amines include 1,8-diazabicyclo(5,4,0)undecene-7, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol. Examples of imidazole and its derivatives include 1-cyanoethyl-2-phenylimidazole, 2-phenylimidazole, 2-ethyl-4(5)-methylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazole], 1-cyanoethyl ..., 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenyl Examples include 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and adducts of epoxy resins and the above imidazoles, or polymer-encapsulated imidazole.

[0053] Examples of organic phosphines include tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine, and phenylphosphine. Examples of phosphonium salts include tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyltriphenylborate, and tetrabutylphosphonium tetrabutylborate. Examples of tetraphenylboron salts include 2-ethyl-4-methylimidazole tetraphenylborate and N-methylmorpholine tetraphenylborate. These curing agents may be used alone or in any combination and ratio of two or more kinds.

[0054] When the liquid composition of the present invention contains a curing agent, the content of the curing agent is preferably in the range of 0.8 to 2.0, more preferably 0.8 to 1.5, in terms of the equivalent ratio of the epoxy groups in the epoxy resin to the functional groups in the curing agent (functional groups in the curing agent / epoxy groups in the epoxy resin), in the case of a phenol-based curing agent, an amine-based curing agent, or an acid anhydride-based curing agent, since influences due to residual unreacted epoxy groups or functional groups of the curing agent are unlikely to occur. When the curing agent is an amide curing agent, a tertiary amine, imidazole and its derivatives, organic phosphines, phosphonium salts, tetraphenyl boron salts, organic acid dihydrazides, boron halide amine complexes, polymercaptan curing agents, isocyanate curing agents, blocked isocyanate curing agents, etc., it is preferably used in an amount of 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the epoxy resin, while it is preferably used in an amount of 20 parts by mass or less, more preferably 10 parts by mass or less. In the case of a dicyandiamine compound, it is preferably used in an amount of 0.1 part by mass or more, more preferably 0.5 part by mass or more, relative to 100 parts by mass of the epoxy resin, while it is preferably used in an amount of 10 parts by mass or less, more preferably 6 parts by mass or less.

[0055] (Cure accelerator) The resin composition of the present invention preferably further contains a curing accelerator. By containing the curing accelerator, it is possible to shorten the curing time and lower the curing temperature. The curing accelerator is not particularly limited, and examples thereof include organic phosphines, phosphorus compounds such as phosphonium salts, tetraphenyl boron salts, organic acid dihydrazides, and boron halide amine complexes. These curing accelerators may be used alone or in any combination and ratio of two or more. The curing accelerator is preferably used in an amount of 0.1 to 20 parts by mass relative to 100 parts by mass of the total epoxy resin components. More preferably, it is 0.5 parts by mass or more, and even more preferably, it is 1 part by mass or more, while it is preferably 15 parts by mass or less, and even more preferably, it is 10 parts by mass or less. When the content of the curing accelerator is equal to or more than the lower limit, a good curing acceleration effect can be obtained, while when the content is equal to or less than the upper limit, the desired curing properties are easily obtained.

[0056] (Polyimide resin) As the polyimide resin used in the present invention, a polyimide obtained from a tetracarboxylic dianhydride and a diamine, in particular an aromatic polyimide obtained from an aromatic tetracarboxylic dianhydride and an aromatic diamine, is preferred, since the thermal expansion coefficient of the resin composite material is likely to be low and the properties such as heat resistance, mechanical strength, electrical properties, and solvent resistance are excellent. More specifically, it is preferable to use a polyimide powder obtained by spraying a polyimide precursor solution onto a polyimide resin powder obtained by polymerizing and imidizing an aromatic tetracarboxylic acid component and p-phenylenediamine, and granulating the polyimide powder, and then combine the polyimide powder with a filler to form a resin composite material. The polyimide powder is granulated by bonding the polyimide powder particles together with the polyimide precursor, and the polyimide precursor acts as a binder in the aggregate. For example, a polyamic acid is used as the polyimide precursor, and the polyimide precursor solution used as the raw material is a polyamic acid produced by reacting a tetracarboxylic dianhydride with a diamine in the presence of a basic compound having a pKa of 7.5 or more using water and / or an alcohol-based solvent as a reaction solvent.

[0057] (Dispersant) Dispersants are mainly added to resin compositions containing a resin with a large polarity difference and a filler such as zeolite to improve the interface state between the two and increase compatibility, which can produce effects such as lowering viscosity, improving the dispersibility of the filler, and preventing filler aggregation and sedimentation. The resin composition of the present invention contains zeolite. Zeolite has a large specific surface area due to its porous structure, and when it is blended in a large amount, the viscosity of the resin composition tends to increase. In the present invention, the resin composition contains a dispersant having at least one functional group of an amino group or an amine salt, thereby suppressing the increase in viscosity of the resin composition and achieving a low thermal expansion coefficient of the cured product.

[0058] The dispersant in the present invention preferably has an amino group at the end from the viewpoint of reducing the viscosity when the resin composition is in a liquid state. The amine salt may be modified with an acid group such as phosphoric acid. In an embodiment of the present invention, the use of a specific dispersant can prevent the viscosity of the resin composition from increasing while using zeolite as an inorganic filler.

[0059] Examples of the dispersant include acrylic dispersants and polymer dispersants. Here, the term "polymer dispersant" refers to a dispersant with a weight average molecular weight of 1,000 or more. The dispersant is preferably a polymer dispersant. The main chain skeleton of the polymer dispersant is not particularly limited, but examples thereof include polyurethane skeleton, polyacrylic skeleton, polyester skeleton, polyamide skeleton, polyimide skeleton, polyurea skeleton, etc., and from the viewpoint of storage stability, polyurethane skeleton, polyacrylic skeleton, and polyester skeleton are preferred. The structure of the polymer dispersant is also not particularly limited, but examples thereof include random structure, block structure, comb structure, star structure, etc., and similarly, from the viewpoint of storage stability, block structure or comb structure is preferred. In addition, the dispersant is preferably a solvent-free dispersant, particularly a solvent-free polymer dispersant, which does not contain a solvent. By using a dispersant that does not contain a solvent, it is possible to prevent the dispersant from volatilizing and causing voids when the composition is cured by heating. The dispersant may be a commercially available product. Examples of commercially available dispersants include the following dispersants, and among these, a dispersant having at least one functional group of an amino group or an amine salt may be used.

[0060] Commercially available polymeric dispersants include 101, 102, 103, 106, 108, 109, 110, 111, 112, 116, 130, 140, 142, 145, 161, 162, 163, 164, 166, 167, 168, 170, 171, 174, 108, 182, 183, 184, 185, 2000, 2001, 2008, 2020, 2050, 2070, 2096, 2150, 2152, and 2155 of the DISPERBYK wetting dispersant series sold by BYK-Chemie, and 4008 of the EFKA series sold by BASF Japan. 4009, 4010, 4015, 4020, 4046, 4047, 4050, 4055, 4060, 4080, 4300, 4330, 4340, 4400, 4401, 4402, 4403, 4406, 4800, 5010, 5044, 5054, 5055, 5063, 5064, 5065, 5066, 5070, 5244, 3000, 5000, 11200, 13240, 13650, 13940, 16000, 17000, 18000, 20000, 21000, 24000SC, 24 000GR, 26000, 28000, 31845, 32000, 32500, 32550, 32600, 33000, 34750, 35100, 35200, 36000, 36600, 37500, 38500, 39000, 53095, 54000, 55000, 56000, 71000, 1210, 1220, 1831, 1850, 1860, 2100, 2150, 2200, 7004, KS-260, KS-273N, KS-860, KS-873N, PW-36, DN-900 of the DISPARLON series available from Kusumoto Chemicals Co., Ltd. DA-234, DA-325, DA-375, DA-550, DA-1200, DA-1401, DA-7301, PB-711, PB-821, PB-822, PN-411, PA-111 of the Ajisper series available from Ajinomoto Co., Inc., 104A, 104C, 104E, 104H, 104S, 104BC, 104DPM, 104PA, 104PG-50, 420, 440, DF110D, DF110L, DF37, DF58, DF75, DF210, CT111, CT121 of the Surfynol series available from Air Products, Inc.Examples of such compounds include CT131, CT136, GA, TG, TGE, STG and E1004 of the Olfin series available from Nissin Chemical Industry Co., Ltd., 70, 2120, and 2190 of the SN Sparse series manufactured by San Nopco Ltd., the Adekacol and Adekatol series available from ADEKA Corporation, the Sannonik series, Naroacty CL series, Emulmin series, Newpol PE series, Ionette M series, Ionette D series, Ionette S series, Ionette T series, and Sunseparator 100 available from Sanyo Chemical Industries, Ltd., and the like.

[0061] The content of the dispersant in the present invention is preferably high, for example, in the case where the resin composition is liquid, in order to easily disperse the zeolite uniformly. On the other hand, the content of the dispersant is preferably low, in order to prevent an increase in the thermal expansion coefficient due to phase separation between the zeolite, which is an inorganic filler, and the resin, such as an epoxy resin. Since the resin composition is easily filled into a narrow space and easily has a low thermal expansion coefficient after curing, the content of the dispersant is preferably 0.1% by mass or more and 30% by mass or less, more preferably 0.1% by mass or more and 25% by mass or less, based on the total amount of the composition.

[0062] <Water absorption rate> The resin composition of the present invention has a water absorption rate of 15% or less when cured to a gel fraction of 80% or more. If the water absorption rate is 15% or less, even when the resin composition is used as a part of an electronic component such as an underfill material, problems caused by hygroscopicity do not occur. From the above viewpoint, the smaller the water absorption rate, the more preferable it is, and it is preferably 12% or less, and more preferably 10% or less. The water absorption rate can be measured by the method described in the Examples.

[0063] <Average coefficient of thermal expansion (CTE)> The resin composition of the present invention has an average thermal expansion coefficient of 35 ppm / K or less when cured to a gel fraction of 80% or more. When the average thermal expansion coefficient is 35 ppm / K or less, the composition has excellent heat resistance, such as thermal cycle resistance, and durability. Therefore, even when the composition is used as a part of an electronic component such as an underfill material, material destruction due to thermal expansion does not occur. From the above viewpoint, the smaller the average thermal expansion coefficient, the more preferable it is, and it is preferably 33 ppm / K or less, and more preferably 30 ppm / K or less. In addition, in terms of being less likely to deform due to the surrounding temperature environment or heat generation, it is preferable that the average thermal expansion coefficient is low when the composition is cured to a gel fraction of 80% or more. On the other hand, in order to prevent damage due to differences in average thermal expansion with the surrounding members, it is preferable that the average thermal expansion coefficient is close to that of the surrounding members. Therefore, when the liquid composition is used as an underfill material or the like in the manufacture of semiconductor devices, it is preferable that the average thermal expansion coefficient is close to that of the semiconductor substrate (e.g., 3 to 4 ppm / K). From the above viewpoints, the liquid composition according to the present invention, when cured to a gel fraction of 80% or more, preferably has an average coefficient of thermal expansion (CTE) of 0 ppm / K or more, more preferably 2 ppm / K or more, even more preferably 4 ppm / K or more, and particularly preferably 10 ppm / K or more.

[0064] The average coefficient of thermal expansion (CTE) is calculated from the slope of the tangent line of the change in the length of a sample measured at 25 to 100°C using a compression method based on thermomechanical analysis in accordance with JIS K7197 (2012).

[0065] (glass transition temperature) The glass transition temperature (Tg) of the epoxy resin composite material obtained by curing the liquid composition according to the present invention is not particularly limited. For example, when the underfill material has a high Tg, the part sealed with the underfill material is considered to be preferable because it has high bump protection at high temperatures and excellent thermal cycle resistance (see, for example, JP 2017-110146 A). From such a viewpoint, the glass transition temperature (Tg) of the cured product of the liquid composition according to the present invention when cured is preferably 50° C. or higher, more preferably 80° C. or higher. Furthermore, since warping at room temperature (23° C.) tends to be less likely to occur when the glass transition temperature is 150° C. or lower, the glass transition temperature (Tg) is preferably 50 to 150° C., and more preferably 80 to 150° C. The glass transition temperature (Tg) can be measured by a thermomechanical analyzer (TMA).

[0066] (Method of producing liquid composition) The liquid composition according to the present invention can usually be obtained by mixing and kneading the epoxy resin, the zeolite according to the present invention, and the curing agent, dispersant, reactive diluent, and other additive components used as necessary using a vacuum mixer, mixing roll, planetary mixer, etc., and degassing as necessary. The order of mixing these components is arbitrary as long as there are no particular problems such as the occurrence of reactions or precipitation, and any two or more of the constituent components may be mixed in advance and then the remaining components may be mixed, or all of the components may be mixed at once.

[0067] The liquid composition of the present invention is preferably used as a liquid sealant, and in this case, the epoxy resin composite material formed by curing the liquid composition preferably serves as a sealant. The liquid sealant may be used as a sealant that fills gaps formed in components and then hardens to fill the gaps. In addition, the liquid sealant may be used as a sealant for filling gaps between components by, for example, applying the liquid sealant onto various components, overlaying another component on the liquid sealant, and then appropriately curing the liquid sealant. In this case, the liquid sealant may be appropriately cured to a B-stage before overlaying the other component. Among these, the liquid composition of the present invention is preferably used for filling a gap and curing it. That is, it is preferable to produce a sealant by filling a gap with the liquid composition of the present invention and then curing it. The liquid composition of the present invention has a low viscosity, and can be filled into even a narrow gap without generating voids.

[0068] The liquid composition of the present invention is preferably used as a liquid sealant, and particularly preferably used as an underfill material. The underfill material is preferably used in the manufacture of electric devices, particularly semiconductor devices, and is preferably used to fill gaps formed between a substrate and a semiconductor chip, between substrates, between semiconductor chips, etc. The substrate may be a known substrate, and may be a substrate made of an organic material such as an epoxy resin substrate or a phenol resin substrate. The semiconductor chip may be formed from a semiconductor substrate such as a silicon substrate. The liquid composition of the present invention has a low coefficient of thermal expansion when cured, and when used as an underfill material, the difference in thermal expansion coefficient between the composition and semiconductor substrates and the like is reduced, thereby improving thermal cycle resistance and the like.

[0069] The underfill material is preferably used as a sealant that fills the gap between the substrate and the semiconductor chip in a laminate in which the semiconductor chip is mounted on the substrate, and then hardens by heating to seal the gap between the substrate and the chip. In this case, the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via bumps by, for example, reflow before the underfill material is filled.

[0070] The underfill material may be used in the manufacture of semiconductor devices by the pre-apply method. Specifically, on the surface of a semiconductor chip on which a plurality of bumps are formed, the underfill material is filled between the plurality of bumps to form an underfill layer. Here, the filled underfill material may be B-staged as necessary. Thereafter, the semiconductor chip on which the underfill layer is formed may be placed on the surface of the substrate with the surface on which the underfill layer is formed facing the substrate. Next, the underfill layer is hardened by heating and pressing, etc. to become an encapsulant, and the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via the bumps.

[0071] In the pre-apply method, an underfill material may be applied to the surface of a substrate on which a wiring pattern is formed to form an underfill layer. Here, the applied underfill layer may be B-staged as necessary. Then, the semiconductor chip on which the bumps are formed may be placed on the substrate on which the underfill layer is formed, with the surface on which the bumps are formed facing the surface of the substrate on which the underfill layer is formed. Then, the underfill layer is hardened by heating and pressing to become an encapsulant, and the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via the bumps.

[0072] In the above description, the underfill material is used as a sealant to fill the gap between the substrate and the semiconductor chip, but the use of the underfill material is not particularly limited, and the underfill material may be used to fill the gap between semiconductor chips, or as a sealant to fill the gap between substrates, etc. Furthermore, the substrate is not limited to a substrate made of an organic material, and may be a semiconductor substrate, etc.

[0073] <Synthetic raw material gel> The method for producing the zeolite contained in the resin composition of the present invention will be described below. The synthesis raw material gel for producing the zeolite of the present invention contains a silicon atom raw material, an aluminum atom raw material, and water. The raw materials constituting the synthesis raw material gel will be described in detail below.

[0074] (Silicon atom source) The silicon atom source used in the present invention is not particularly limited, and various known substances can be used. Specifically, amorphous silica such as colloidal silica, amorphous silica, fumed silica, and sodium silicate, silane oligomers obtained by hydrolysis and polymerization of alkoxysilanes such as trimethylethoxysilane and tetraethylorthosilicate, silica sol, aluminosilicate gel, and zeolite can be used. These may be used alone or in any combination and ratio of two or more. Among these, amorphous silica is preferred because it is easily dissolved in water and is inexpensive. From the viewpoints of being easily mixed uniformly with other raw materials and being easily dissolved in water, colloidal silica, silane oligomer, and aluminosilicate gel are preferred, and colloidal silica is particularly preferred.

[0075] (Aluminum atom source) The aluminum atom source is preferably a compound that is easily soluble in water, and is also preferably a compound that is easily miscible with the silicon atom source and that is easily soluble so as to provide a Si / Al ratio suitable for zeolite crystallization during the aging and hydrothermal synthesis steps. From the above viewpoints, preferred aluminum atom raw materials are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudo-boehmite, aluminum alkoxide, etc. These may be used alone or in any combination of two or more kinds in any ratio. Among these, particularly preferred are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure. The aluminum atom raw material is preferably amorphous, and among the above, amorphous aluminum hydroxide is particularly preferred.

[0076] (water) When using a seed zeolite described later, the amount of water used is usually 5 or more, preferably 7 or more, more preferably 9 or more, and even more preferably 10 or more in terms of the molar ratio to silicon (Si) contained in the raw material composition other than the seed zeolite, from the viewpoint of facilitating crystal formation. By setting the amount of water within this range, crystal formation is facilitated. In addition, by hydrothermally synthesizing zeolite under conditions in which the amount of water is increased and the raw material concentration is diluted, it is easy to produce zeolite with a large particle size. In terms of facilitating the cost reduction effect for waste liquid treatment, the molar ratio to silicon (Si) is usually 50 or less, preferably 40 or less, more preferably 30 or less, and even more preferably 25 or less.

[0077] (Organic structure directing agent) The synthesis raw material gel of the present invention preferably contains an organic structure-directing agent in addition to the silicon atom raw material, the aluminum atom raw material, and water. As the organic structure directing agent, various known substances such as tetraethylammonium hydroxide (TEAOH) and tetrapropylammonium hydroxide (TPAOH) can be used. Among these, N,N,N-trimethyl-1-adamantaammonium hydroxide (TMAdaOH) is preferred. The amount of the organic structure directing agent used is, in terms of molar ratio to silicon (Si) contained in the synthesis raw material gel, usually 0.01 or more, preferably 0.02 or more, more preferably 0.03 or more, particularly preferably 0.04 or more, and most preferably 0.05 or more. On the other hand, it is usually 1 or less, preferably 0.6 or less, more preferably 0.55 or less, and even more preferably 0.5 or less. By using within this range, it is thought that high-purity spherical zeolite with few by-products is easily grown.

[0078] (Alkali metal atom source) Zeolite may be produced using an alkali metal atom raw material. When using an alkali metal atom raw material, the alkali metal atom is not particularly limited, and any known alkali metal atom used in the synthesis of zeolite may be used, but at least one alkali metal selected from the group consisting of lithium, sodium, potassium, rubidium, and cesium is preferred. Note that multiple types of alkali metal atoms may be used.

[0079] (Seed zeolite) In the method for producing zeolite, a seed zeolite may be used. When a seed zeolite is used, one type may be used alone, or two or more types may be used in any combination and ratio.

[0080] The method for producing a zeolite of the present invention includes a mixing step, an aging step, and a hydrothermal synthesis step. Each step will be described in detail below. In the production of zeolite, in addition to the above-mentioned components, components such as an acid component for accelerating the reaction and a metal stabilizer such as polyamine may be added at any step as necessary.

[0081] <Mixing process> More specifically, this is a step of preparing a synthesis raw material gel by mixing the above-mentioned silicon atom raw material, aluminum atom raw material, water, an organic structure directing agent added as necessary, an alkali metal atom raw material, and seed crystal zeolite. When preparing the synthesis raw material gel, the order of addition of each raw material is not particularly limited, but from the viewpoint of easy control of viscosity change during mixing, the silicon atom raw material, the aluminum atom raw material, and the alkali metal atom raw material are added to water and dissolved or dispersed. An organic structure directing agent is added as necessary, but it may be blended in the synthesis raw material gel from the beginning, or it may be added after the aging process described below and immediately before hydrothermal synthesis.

[0082] (Mixed condition) The mixing conditions for preparing the synthesis raw material gel are not particularly limited, but from the viewpoint of purity and uniformity, long mixing times are preferable. On the other hand, from the viewpoint of production efficiency, short mixing times are preferable. Therefore, the mixing time is preferably 30 s or more, and particularly preferably 60 s or more. On the other hand, 7200 s or less is preferable, 1800 s or less is more preferable, and 600 s or less is particularly preferable. Mixing with stirring is preferred from the viewpoint of facilitating the preparation of a uniform synthesis raw material gel.

[0083] <Aging process> The raw material composition obtained by adding a surfactant to the synthesis raw material gel as described above may be hydrothermally synthesized immediately after preparation, but in order to obtain a zeolite with higher crystallinity, it is preferable to age the raw material for a certain period of time under a predetermined temperature condition. In particular, when the reaction is scaled up, it is preferable to age the raw material while stirring it for a certain period of time, since this improves the stirrability and makes the raw material more homogeneous. The temperature for aging is usually 100°C or less, preferably 95°C or less, more preferably 90°C or less, and although there is no particular limit to the lower limit, the temperature for aging is usually 0°C or more, preferably 10°C or more. The aging temperature may be constant during aging, or may be changed stepwise or continuously. The aging time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and on the other hand, is usually 30 days or less, preferably 10 days or less, and more preferably 4 days or less.

[0084] <Hydrothermal synthesis process> Next, the obtained raw material composition is subjected to hydrothermal synthesis. Hydrothermal synthesis is usually carried out by placing the raw material composition prepared as described above or an aqueous gel obtained by maturing the raw material composition in a pressure-resistant container, and maintaining the mixture at a predetermined temperature under self-generated pressure or under gas pressure to an extent that does not inhibit crystallization, while stirring, rotating or rocking the container, or leaving it stationary. In order to increase the reaction rate, the reaction temperature during hydrothermal synthesis is preferably 120°C or higher, more preferably 130°C or higher, even more preferably 140°C or higher, and particularly preferably 150°C or higher. On the other hand, it is usually 230°C or lower, preferably 220°C or lower, more preferably 200°C or lower, and even more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and on the other hand, it is usually 30 days or less, preferably 10 days or less, more preferably 7 days or less, and even more preferably 5 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. The reason why the zeolite production method according to the present invention can produce particularly preferable zeolites is believed to be that the surfactant is adsorbed onto the surface of the growing zeolite crystals, causing the zeolite to grow while creating a state close to a spherical micelle structure.

[0085] <Drying process> After the hydrothermal synthesis, the zeolite is separated from the composition after the hydrothermal synthesis (hydrothermal synthesis reaction liquid). The method of separation is not particularly limited, but it is usually separated by washing with water, filtration, decantation, direct drying, etc. Even if it is separated by filtration or decantation, it is usually dried after that. Drying conditions are not particularly limited, and for example, the drying temperature is preferably 50° C. or higher and 200° C. or lower, and more preferably 70° C. or higher and 150° C. or lower. The drying atmosphere is not particularly limited, and the drying may be performed in air or in an inert atmosphere such as nitrogen or argon.

[0086] <Firing process> The dried zeolite is subjected to calcination or the like in order to remove the structure-directing agent and the like used during the production. The calcination temperature is usually preferably 300° C. to 1000° C. Calcination at 300° C. or higher can remove the organic structure directing agent, while calcination at 1000° C. or lower does not impair the physical properties of the zeolite. From the above viewpoints, the calcination temperature is preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher, and is preferably 900° C. or lower, more preferably 800° C. or lower, and even more preferably 700° C. or lower. The atmosphere for the firing is not particularly limited, and the firing may be performed in air or in an inert atmosphere such as nitrogen or argon. The calcination method is not particularly limited, and a muffle furnace, a kiln, a fluidized calcination furnace, etc. can be used, but the calcination method using the gas is preferable. The gas flow rate is not particularly limited, but the amount of gas flow per 1 g of powder is preferably in the range of 0.1 ml / min to 100 ml / min, and calcination is preferably performed under a gas flow of 5 ml / min to 20 ml / min.

[0087] (Viscosity of Resin Composition) The resin composition of the present invention is a composition having fluidity at room temperature (23°C) (hereinafter, may be referred to as "liquid composition"). The viscosity of the resin composition of the present invention is preferably low in terms of ease of filling a narrow space with the resin composition. On the other hand, it is preferable that the viscosity is high in terms of preventing dripping during filling of the composition. The viscosity of the liquid composition at 23°C is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, even more preferably 5 Pa·s or more, and particularly preferably 10 Pa·s or more. On the other hand, it is preferably 250 Pa·s or less, more preferably 200 Pa·s or less, even more preferably 150 Pa·s or less, particularly preferably 60 Pa·s or less, and especially preferably 30 Pa·s or less. The viscosity at 23°C is most preferably 1 Pa·s or more and 30 Pa·s or less. The viscosity of the liquid composition can be measured in the same manner as the viscosity measurement method for epoxy resins described above. The viscosity of the liquid composition used in the present invention at 23°C may be measured using a B-type rotational viscometer, which is one of the single cylinder rotational viscometer methods. For the B-type rotational viscometer, for example, the one described in the Examples may be used. EXAMPLES

[0088] The production method of the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited in any way. The evaluations and measurements in the examples were carried out by the methods shown below.

[0089] (Evaluation method) (1) Water absorption rate (%) The resin compositions obtained in each of the Examples and Comparative Examples were cured to a gel fraction of 80% or more. The cured products were then kept in a drying oven at 125°C for 3 hours, and then in a constant temperature and humidity chamber adjusted to 85°C and 85% humidity for 3 hours. The cured products were then evaluated based on the rate of weight change.

[0090] (2) Average coefficient of thermal expansion (CTE) The resin compositions obtained in each of the Examples and Comparative Examples were cured to a gel fraction of 80% or more, and the cured products were measured by thermomechanical analysis according to a method in accordance with JIS K7197 (2012). A thermomechanical analyzer (TMASS7100, manufactured by Hitachi High-Tech Science Corporation) was used to measure the cured products by a compression method. Specifically, the cured products were cut into pieces of φ6 mm×10 mm in size, and the temperature was lowered from 200° C. to 20° C. at a rate of 5° C. / min using a thermomechanical analyzer by a compression method, and the temperature change in the amount of change in the sample length from 25 to 100° C. was measured, and the slope of the tangent was taken as the average coefficient of thermal expansion (CTE).

[0091] (Materials used) (A) Filler (a) CHA-type zeolite: The zeolite prepared by the method described in the Examples was used. (b) Silica: Admatechs Co., Ltd. "SC2053-SQ" (B) Surface treatment agent (c) Silane coupling agent; Shin-Etsu Chemical Co., Ltd. "KBM-1083" (d) Epoxy resin; "jER630" manufactured by Mitsubishi Chemical Corporation (e) Polyvinyl alcohol; "Poval" manufactured by Kuraray Co., Ltd. (f) Fluorine resin emulsion; AGC's "Lumiflon FE4300" (C) Matrix resin (g) Epoxy resin; "jER630" manufactured by Mitsubishi Chemical Corporation (D) Other (h) Epoxy resin hardener; "Rikacid HNA-100" manufactured by New Japan Chemical Co., Ltd. (i) Curing accelerator: "Hishicolin PX-4MP" manufactured by Nippon Chemical Industry Co., Ltd.

[0092] [Example 1] (Synthesis of CHA-type zeolite) Into the vessel were sequentially added N,N,N-trimethyl-1-adamantylammonium hydroxide (TMAdaOH) manufactured by Seichem Co., Ltd. as a structure directing agent (SDA), "Kyoward 200S" manufactured by Kyowa Chemical Industry Co., Ltd. as aluminum hydroxide, and "AEROSIL200" manufactured by Nippon Aerosil Co., Ltd. as silica. The composition and molar ratio of the obtained mixture was SiO2:Al2O3:TMAdaOH:H2O=1.0:0.025:0.4:20. After thorough mixing, the obtained mixture was placed in a pressure-resistant container and subjected to hydrothermal synthesis in an oven at 150°C for 48 hours. After suction filtration and washing, it was dried. The obtained powder was fired at 600°C for 6 hours under air flow to remove the TMAdaOH, which is a structure-directing agent (SDA), to obtain CHA-type zeolite. The obtained zeolite was a zeolite in which the particle diameter of each particle was in the range of 1.0 μm to 10 μm, and the average primary particle diameter was 3.1 μm. The average primary particle diameter was the average value of the particle diameters of 50 randomly selected primary particles. In addition, the average thermal expansion coefficient at 50 to 100°C was -9.0 ppm / K, the average thermal expansion coefficient at 50 to 350°C was -17.0 ppm / K, the Si / Al2 ratio was 27.8, the sphericity was 0.85, the circularity was 0.845, the c-axis length was 14.67 Å, ​​and the counter cation was a proton type.

[0093] (Zeolite Coating Treatment) The CHA-type zeolite prepared by the above method was treated with a silane coupling agent (KBM-1083, manufactured by Shin-Etsu Chemical Co., Ltd.) by the following procedure. Acetone was added to the CHA zeolite and stirred in a mixer to form a slurry. Next, a silane coupling agent was added to the slurry so that the CHA zeolite was 1% by mass, and the mixture was stirred for 10 minutes. After that, the mixture was filtered using filter paper, and the CHA zeolite treated with the silane coupling agent was taken out and washed with methanol. The mixture was then spread thinly on a tray and dried at 120°C for 90 minutes to obtain a coated CHA zeolite.

[0094] (Preparation of Resin Composition) 50 parts by mass of the coated CHA-type zeolite, 21 parts by mass of epoxy resin, 28 parts by mass of epoxy resin curing agent, and 1 part by mass of curing accelerator were mixed and / or kneaded using a Thinky Mixer ARV-310P (a planetary stirring mixer manufactured by Thinky Co., Ltd.) to obtain a resin composition. The results of evaluation of the resin composition by the above-mentioned method are shown in Table 1.

[0095] [Example 2] A resin composition was obtained in the same manner as in Example 1, except that an epoxy resin (manufactured by Mitsubishi Chemical Corporation, jER630) was used as the surface treatment agent instead of the silane coupling agent in Example 1. The evaluation results are shown in Table 1.

[0096] [Example 3] A resin composition was obtained in the same manner as in Example 1, except that polyvinyl alcohol (Poval, manufactured by Kuraray Co., Ltd.) was used as the surface treatment agent instead of the silane coupling agent in Example 1. The evaluation results are shown in Table 1.

[0097] [Comparative Example 1] A resin composition was obtained in the same manner as in Example 1, except that the surface treatment of the zeolite was not carried out. The evaluation results are shown in Table 1.

[0098] [Comparative Example 2] A resin composition was obtained in the same manner as in Comparative Example 1, except that silica (manufactured by Admatechs Co., Ltd., "SC2053-SQ" (average particle size 0.5 μm)) was used instead of zeolite. The evaluation results are shown in Table 1.

[0099] [Comparative Example 3] A resin composition was obtained in the same manner as in Example 1, except that silica (manufactured by Admatechs, "SC2053-SQ" (average particle size 0.5 μm)) was used instead of zeolite, and a fluororesin emulsion (manufactured by AGC, Lumiflon FE4300) was used instead of the silane coupling agent as the surface treatment agent. The evaluation results are shown in Table 1.

[0100] [Table 1]

[0101] The resin compositions of Examples 1 to 3 used zeolite as a filler, and the zeolite was coated with a surface treatment agent, so that the water absorption rate was low and the average coefficient of thermal expansion (CTE) was small. The difference in water absorption rate between Examples 1 to 3 and Comparative Example 1 was large and significant. On the other hand, with regard to the CTE, since zeolite was used as the filler in Examples 1 to 3 and Comparative Example 1, extremely superior values ​​were shown as compared with Comparative Examples 2 and 3 in which silica was used as the filler. From the above, it is clear that the resin composition of the present invention has extremely excellent performance, including a small average coefficient of thermal expansion (CTE) and a low water absorption rate. [Industrial Applicability]

[0102] INDUSTRIAL APPLICABILITY The resin composition of the present invention has a small average coefficient of thermal expansion (CTE) and a low water absorption rate, and is therefore extremely useful as an underfill material. When considering its use as a material for electronic components, the resin composition has extremely high industrial value.

Claims

1. A resin composition containing zeolite coated with a surface treatment agent and a matrix resin, the resin composition having a water absorption rate of 15% or less when cured to a gel fraction of 80% or more, and an average thermal expansion coefficient of 35 ppm / K or less when cured to a gel fraction of 80% or more.

2. The resin composition of claim 1 , wherein the zeolite has a CBU of d6r.

3. The resin composition according to claim 1 , wherein the zeolite has a structure containing eight or fewer oxygen ring members.

4. The resin composition according to claim 1 , wherein the zeolite is a CHA-type zeolite.

5. The resin composition according to claim 1, wherein the surface treatment agent is at least one selected from the group consisting of a silane coupling agent, an epoxy resin, and a polyvinyl alcohol resin.

6. The resin composition according to claim 1 , wherein the matrix resin is an epoxy resin.

7. The resin composition according to claim 1, wherein the content of the zeolite in the resin composition is 25% by mass or more and 90% by mass or less in terms of solid matter.

8. The resin composition according to claim 1 , wherein the content of the matrix resin in the resin composition is 5% by mass or more and 50% by mass or less in terms of solid matter.

9. The resin composition according to any one of claims 1 to 8, which is used for an underfill material.

Citation Information

Patent Citations

  • Under fill material for flip chip type semiconductor device, the flip chip type semiconductor device using the same and method for producing the device

    JP2007056070A

Cited By

  • Field test device and method for free expansion rate and permeability coefficient of expansive soil

    CN120142612A